2020
DOI: 10.1101/2020.08.05.20169128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal analysis of clinical serology assay performance and neutralising antibody levels in COVID19 convalescents

Abstract: Objectives:To investigate longitudinal trajectory of SARS-CoV-2 neutralising antibodies and the performance of serological assays in diagnosing prior infection and predicting serum neutralisation titres with time Design Retrospective longitudinal analysis of a COVID19 case cohort . Setting NHS outpatient clinics Participants Individuals with RT-PCR diagnosed SARS-CoV-2 infection that did not require hospitalization Main outcome measures The sensitivity with which prior infection was detected and quantit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
104
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 44 publications
(58 reference statements)
21
104
0
1
Order By: Relevance
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref. 12 ) and 5/80 (ref.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The magnitude of the following decline in neutralizing antibody titres reported here is similar to that observed in several newly reported pre-prints 12,13,20,31,[34][35][36][37][38][39] . In these studies, similar to our observations, those who generated a high neutralizing antibody titre still had high neutralizing antibody titres regardless of the initial decline 12,13,31,35,39 and, for those with lower disease severity, two studies reported 7/34 (ref. 12 ) and 5/80 (ref.…”
Section: Discussionsupporting
confidence: 89%
“…this is subsequently followed by a decline in virus-specific antibodies as these cells die. We observed a wide range of peak neutralizing antibody titres (98-32,000), similar to other cross-sectional cohorts 21,4,31 , and disease severity was associated with higher neutralizing antibody titres. It is not clear yet why neutralizing antibody responses correlate with disease severity 32 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other assays in which antibody reactivity wanes over time are less suited to detect previously-infected individuals but tend to correlate more closely with neutralizing antibody titer. 18 In our study, higher S/C values for spike Total Ig were associated with male sex, non-Hispanic Native American/Alaskan and Black race/ethnicity, and Hispanic ethnicity. Whether this correlates with the severity of infection or indicates a more vigorous immunologic response remains to be determined.…”
Section: Sars-cov-2 Binding Totalsupporting
confidence: 49%
“…Assuming all 133 samples were true positives the sensitivity of the Abbott N IgG assay was 77.4% (95%CI 69.6% to 83.7%) on asymptomatic blood donor serosurveillance samples. The Roche assay detects total Ig and the signal is more stable than the Abbott assay 22 . As samples in July were donated four months into the on-going epidemic in São Paulo, the false negatives on the Abbott assay include both cases that did not initially seroconvert ("serosilent" infections), as well as remote infections with subsequent seroreversion.…”
Section: Sars-cov-2 Antibody Dynamics and Serology Assay Validationmentioning
confidence: 99%